Averroes, Maimónides, y la crisis en la comunidad judía medieval - Chahlane, Ahmed (Anales del Seminario de Historia de la Filosofía, 2005)
The translation of Maimonides’ main work, the Guide of the Perplexed, from rabic into Hebrew had a wide and long-lasting influence. It caused a social crisis nside the Jewish communities living under Christian rule, it opened the doors of he philosophy of Averroes and Aristotle to them, and originated the Jewish verroist movement as well as the adversary one. Since Algazel represented the tra- itional point of view that opposed to philosophy and was attacked by Averroes, hahlane argues that the Jewish community was interested in Algazel because he as instrumental in the internal polemic against Averroes and Maimonides.